Perbedaan Model dan Teori dalam Ilmu Komunikasi - Bambang A. S. (Humaniora, 2014)
This article aims to describe differences in models and theories of communication and their respective roles. Many students of Communication Studies do not really care because it was considered too elementary. Students tend to focus on the "big things", such as the development of cutting-edge theories and methodologies, which are currently in the direction of qualitative. Fully understand the differences in substantive theory and models, not only will provide clarification, but also understand each scientific term more comprehensively. The study was conducted based on literature study, with critical descriptive writing, it is also expected to give more space in the discussion. Thus, the purpose of writing this article as mentioned above will be sharper and more significant (reaching level universe of discourse).